Revealing Choice Bracketing - Ellis, Andrew; Freeman, David J. (American Economic Review, 2024)
Experiments suggest that people fail to take into account interdependencies between their choices—they do not broadly bracket. Researchers often instead assume people narrowly bracket, but existing designs do not test it. We design a novel experiment and revealed preference tests for how someone brackets their choices. In portfolio allocation under risk, social allocation, and induced-value shopping experiments, 40–43 percent of subjects are consistent with narrow bracketing, and 0–16 percent with broad bracketing. Adjusting for each model’s predictive precision, 74 percent of subjects are best described by narrow bracketing, 13 percent by broad bracketing, and 6 percent by intermediate cases. (JEL D12, D81, D91)